2019
DOI: 10.1108/mip-05-2018-0148
|View full text |Cite
|
Sign up to set email alerts
|

Store love in single brand retailing: the roles of relevant moderators

Abstract: Purpose The purpose of this paper is to investigate how various retail store atmospheric cues can impact store brand loyalty (SBL) via eliciting store brand love. This paper posits that different store brand experiential cues can predict brand love only when the experience is processed based on perceiving the brand as human-like entity, i.e. brand anthropomorphization. Brand love cannot be strongly elicited without the sense of brand anthropomorphization. Moreover, brand love can impact brand loyalty intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 41 publications
4
50
0
8
Order By: Relevance
“…The authors discussed that future researchers can explore the role of additional antecedents like brand image in determining brand love. The effect of brand love on active engagement and loyalty intention was discussed by Sarkar and Sreejesh (2014) and Sarkar et al., (2019), respectively, in their studies. Also, the effect of brand engagement on loyalty intention was studied by Dwivedi (2015).…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…The authors discussed that future researchers can explore the role of additional antecedents like brand image in determining brand love. The effect of brand love on active engagement and loyalty intention was discussed by Sarkar and Sreejesh (2014) and Sarkar et al., (2019), respectively, in their studies. Also, the effect of brand engagement on loyalty intention was studied by Dwivedi (2015).…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…Consumers start defending the brand (Sashittal & Jassawalla, 2019). Moreover, when consumers perceive a brand to be human-like, they start loving it (Sarkar et al, 2019) and defending it (Wang et al, 2019). In their empirical investigations, Rauschnabel and Ahuvia (2014) and Ferreira (2020) confirmed a significant impact of brand anthropomorphism on brand love and brand defense, respectively.…”
Section: Brand Anthropomorphism Brand Love and Brand Defensementioning
confidence: 99%
“…Brand anthropomorphism has been studied within branding literature. However, there is a lack of scales available to measure brand anthropomorphism (Sarkar et al, 2019). While some scholars used physical attributes of a human body, i.e.…”
Section: Brand Anthropomorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, developing brand love is considered as a primary goal for customer relationship marketing (CRM) and brand management (Pawle and Cooper 2006). Accordingly, there has been a substantial amount of academic research on brand love and its relationship to consumer behaviors such as shopping/brand experiences (Pandowo 2016;Sarkar et al 2019), purchase intentions (Fetscherin 2014;Pawle and Cooper 2006), brand loyalty (Alnawas and Alrarifi 2015;Drennan et al 2015;Fournier 1998;Huang 2017;Thomson et al 2005;Wallace et al 2014), brand trust (Albert and Merunka 2013;Langner et al 2015), positive word-of-mouth (Karjaluoto et al 2016;Wallace et al 2014), and willingness to pay (Albert and Merunka 2013;Thomson et al 2005). Fournier (1998) argued that consumers are capable of emotionally bonding with certain brands in a similar manner to developing interpersonal relationships and her claim was supported by later research that found consumers can build emotional connections with brands just like developing love in a relationship (Carroll and Ahuvia 2006;Wallace et al 2014).…”
Section: Introductionmentioning
confidence: 99%